1994
DOI: 10.5694/j.1326-5377.1994.tb127636.x
|View full text |Cite
|
Sign up to set email alerts
|

Mortality associated with anaesthesia in New South Wales, 1984‐1990

Abstract: The Special Committee Investigating Deaths Under Anaesthesia (SCIDUA) reviews all deaths under or within 24 h of anaesthesia in the Australian state of New South Wales, with a population of 5.7 million. The Committee is appointed by the Minister for Health, is legally privileged and provides complete confidentiality of its investigations. Deaths are reported to SCIDU by the State Coroner's Office. The anaesthetist involved in each case then is asked to complete and voluntarily return a questionnaire on the eve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(15 citation statements)
references
References 8 publications
2
12
0
Order By: Relevance
“…Our results are comparable with data from recent studies applying a study method, classification and postoperative observation period similar to ours, in which estimated 24-h perioperative mortality was 20 per 10 000 anaesthetics and anaesthetic mortality 1.9±7.0 per 10 000 anaesthetics) [5,14,18,64,65]. The estimates for 24-h peri-operative mortality (2.5±5 per 10 000 anaesthetics) and anaesthetic mortality (0.3±0.7 per 10 000 anaesthetics) are somewhat smaller if reporting is voluntary [12,13,15,17]. In our study, voluntary data collection probably caused significant underreporting.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…Our results are comparable with data from recent studies applying a study method, classification and postoperative observation period similar to ours, in which estimated 24-h perioperative mortality was 20 per 10 000 anaesthetics and anaesthetic mortality 1.9±7.0 per 10 000 anaesthetics) [5,14,18,64,65]. The estimates for 24-h peri-operative mortality (2.5±5 per 10 000 anaesthetics) and anaesthetic mortality (0.3±0.7 per 10 000 anaesthetics) are somewhat smaller if reporting is voluntary [12,13,15,17]. In our study, voluntary data collection probably caused significant underreporting.…”
Section: Discussionsupporting
confidence: 58%
“…Our data suggest that inadequate preparation may contribute to one-quarter of the anaesthesia-related deaths, against 40±45% in studies with a comparable study design [12,16,17]. In the current study, inadequate preparation was partly associated with organisational factors and`questionable surgery' or`questionable lack of surgery'.…”
Section: Discussionmentioning
confidence: 45%
“…Studies of anaestheticrelated mortality in the 1950s reported an incidence of 2.5-6.4:10 000 deaths [11,21,36]. Since then, data from South Africa have shown a decrease from 4.3:10 000 anaesthetic-related deaths to 0.7:10 000 (1972-87) [21]; from 1:5500 to 1:20 000 in New South Wales (NSW), Australia, from 1960 to 1990 [25], and from 0.3:10 000 to 0.13:10 000 for the whole of Australia from 1985 to 1999 [9,25]. These Australian figures exemplify the difficulties inherent in such statistics, as the NSW rate (with compulsory Coroner reporting for all deaths within 24 h of anaesthesia and surgery) is given as 1: 66 183 in the Australia and New Zealand College of Anaesthetists (ANZCA) report [9], yet the number of procedures estimated by the NSW Committee for the same period is approximately half those calculated by the ANZCA report (J Warden & R Holland pers.…”
Section: Mortalitymentioning
confidence: 99%
“…National studies of mortality that assess the quality of the delivery of care continue to highlight factors that contribute to anaesthetic-related mortality: inadequate pre-operative assessment, preparation and resuscitation; inappropriate anaesthetic technique; inadequate perioperative monitoring; lack of supervision; poor postoperative care [25,35,38].…”
Section: Mortalitymentioning
confidence: 99%
“…Studies of anaesthetic‐related mortality in the 1950s reported an incidence of 2.5–6.4:10 000 deaths [11, 21, 36]. Since then, data from South Africa have shown a decrease from 4.3:10 000 anaesthetic‐related deaths (1956–71) to 0.7:10 000 (1972–87) [21]; from 1:5500 to 1:20 000 in New South Wales (NSW), Australia, from 1960 to 1990 [25], and from 0.3:10 000 to 0.13:10 000 for the whole of Australia from 1985 to 1999 [9, 25]. These Australian figures exemplify the difficulties inherent in such statistics, as the NSW rate (with compulsory Coroner reporting for all deaths within 24 h of anaesthesia and surgery) is given as 1:66 183 in the Australia and New Zealand College of Anaesthetists (ANZCA) report [9], yet the number of procedures estimated by the NSW Committee for the same period is approximately half those calculated by the ANZCA report (J Warden & R Holland pers.…”
Section: Mortalitymentioning
confidence: 99%